Barriers and Enablers to Early Identification, Referral and Access to Geriatric Rehabilitation Post-Hip Fracture: A Theory-Based Descriptive Qualitative Study. (1st September 2021) - Backman, Chantal; Harley, Anne; Papp, Steve; French-Merkley, Veronique; Beaulé, Paul E; Poitras, Stéphane; Dobransky, Johanna; Squires, Janet E
Background: Geriatric hip fracture patients often experience gaps in care including variability in the timing and the choice of an appropriate setting for rehabilitation following hip fracture surgery. Many guidelines recommend standardized processes, including timely access of no later than day 6 to rehabilitation services. A pathway for early identification, referral and access to geriatric rehabilitation post-hip fracture was created to facilitate the implementation. The study aimed to describe the barriers and enablers prior to the implementation of this pathway. Methods: We conducted a qualitative descriptive study consisting of semi-structured interviews with geriatric hip fracture patients (n = 8), caregivers (n = 1), administrators (n = 12) and clinicians (n = 17) in 2 orthopaedics units and a geriatric rehabilitation service. Responses were analysed using a systematic approach, and overarching themes describing the barriers and enablers were identified. Results: The clinicians' and administrators' top barriers to implementation of the pathway were competing demands (n = 24); lack of bed availability, community resources and funding (n = 19); and the need for extended hours and increased staff (n = 16). The top 3 enablers were clear communication with patients (n = 27), awareness of the benefits of geriatric rehabilitation (n = 24) and the need for education and resources to properly use the pathway (n = 15). Common barriers among patients and caregivers included lack of care coordination, overcoming some of their own specific challenges during their transition, gaps in the information they received before discharge, not knowing what questions to ask and lack of resources. Despite these barriers, patients were generally pleased with their transition from the hospital to geriatric rehabilitation. Conclusion: We identified and described key barriers and enablers to early identification, referral and access to geriatric rehabilitation post-hip fracture. These influencing factors provide a basis for the development of a standardized pathway aimed at improving access to rehabilitative care for geriatric hip fracture patients.